PENGARUH HARGA, CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA APLIKASI SHOPEE - Panji Wibisono (2022)
This research is included in quantitative research which aims to find out and prove the effect of price, brand image and product quality on purchasing decisions on the Shopee application. The population used in this study are Shopee application users in the Jakarta area. Sampling used non-probability sampling with a sampling technique that is purposive sampling and obtained a sample of 100 respondents. Data collection was carried out in this study by distributing questionnaires to respondents using the Google Form. The data analysis technique used in this study is descriptive analysis and inferential analysis where the tool for analyzing the data in this study is using SmartPLS version 4.0.8.4. The results obtained in this study are: (1) the price variable has no effect and is not significant on the purchase decision, (2) the brand image variable has no effect and is not significant on the purchase decision, (3) the product quality variable has a significant and significant effect on the purchase decision. Price, brand image and product quality variables contribute 61.4% to purchasing decisions while the remaining 38.6% is influenced by other variables not included in this study such as promotions, service quality and others.